Peningkatan Keterampilan Menulis dengan Media Gambar Terhadap Siswa Kelas I Sekolah Dasar - MARDIYAH, MARDIYAH (Educreative : Jurnal Pendidikan Kreativitas Anak, 2021)
This study aims to provide a depiction of the ptodrd improvement of paragraph writing skills of grade 1 students at SD Negeri 3 Kemranggon, Susukan Subdistrict, Banjarnegara Regency through learning media in the form of images or photos. The method applied is field research that uses case studies, in which students or students will be observed the development or improvement of their writing skills before and after carrying out learning using image media. Data collection techniques conducted in the form of field observations using instruments that have been created with the aim of observing the learning process that occurs in the classroom using learning media in the form of images or photos. The results of this study showed the existence of power levels with an average value of 56.87% at the beginning increased to 66.43% in the first cycle, and in the second cycle increased again to 80.17%, and the value obtained has exceeded the complete value limit of the average value above 65 (KKM)